The effects of additional electrical stimulation combined with repetitive transcranial magnetic stimulation and motor imagery on upper extremity motor recovery in the subacute period after stroke: A preliminary study. Issue 35 (3rd September 2021) - Kang, Ji Hye; Kim, Min-Wook; Park, Kyoung Ha; Choi, Young-Ah
Abstract: Background: To evaluate the therapeutic effects of additional electrical stimulation (ES) combined with low frequency (LF)-repetitive transcranial magnetic stimulation (rTMS) and motor imagery (MI) training on upper extremity (UE) motor function following stroke. Methods: The participants with subacute stroke in the experimental group (n = 8) received LF rTMS + MI + active ES interventions, and those in control group (n = 9) received LF rTMS + MI + sham ES interventions. Interventions were performed 5 days a week for 2 weeks, for a total of 10 sessions. All participants were given the same dosage of conventional rehabilitation during the study period. The primary outcome measure was the UE Fugl-Meyer Assessment (FMA). The secondary outcome measures were the shoulder abduction and finger extension scores, modified Barthel Index, Purdue Pegboard Test, and finger tapping test. All scores were measured before and just after the intervention. Results: After the 2-week intervention period, the FMA and modified Barthel Index scores were improved in both groups compared to baseline assessment (P < .001 in the experimental group and P = .008 in the control group). Of note, the change in FMA scores was significantly higher in the experimental group compared with that of the control group ( P = .04). Conclusion: These results suggest that the use of LF rTMS + MI combined with additional ES lead to greater improvement of UE motor function after stroke. As such, this intervention may be a promising adjuvant therapy in UE motor training.